Vamos falar com a juventude? Culturas juvenis nas escolas de ensino médio: para além do espaço da invisibilidade e da voz silenciada - Oliveira, Karina dos Santos (2024)
It is demonstrated that school is stablished as a primary institution in the process of socialization of subjects, a fact recognized and socially instituted. In any case, it is at school and through it that youth are formed (DAYRELL, 2007). However, by bringing together a multiplicity of identities, practices and cultures, interpersonal conflicts and challenges to deal with such diversity emerge within it. In this sense, this thesis is oriented towards thinking about youth cultures present in high school institutions, highlighting subjective representations, identity constructions, as well as the networks of sociability and belonging that emerge in this dichotomous space of relationships. Focusing on the area of Sociology of Youth, qualitative research aims, through a sociological perspective, to construct a reflection that highlights the young person as a “social subject”. In a more objective way, it seeks to approach the student in “flesh and blood”, in the narrowest sense of the term, an individual who inhabits the classroom and who finds themself in a constant process of self-affirmation in this dubious environment, which can be hostile as well as welcoming, where they seek to claim their right to exist/resist in this space. In this sense, the study makes efforts to understand the young person who is “inside the student”, opposing the established form of “school logic” of standardization, discipline and control. It is worth noting that these social actors are marked above all else by the cycle of puberty and eager entry into the world of adolescence, as well as being permeated by the social, political, cultural, economic and familial context of the world to which they belong, highlighting here their nuances in the production of subjectivities both individual and collective. Therefore, it is extremely important to propose a discussion around this moratorium social category, which is contextualized in the logic of capitalist and neoliberal industrial society. Believing that the image resource has specific sociological meanings and that it serves as a tool for social analysis (FERRO; 2005), it is through drawings, paintings and photographs that we aim to reach this youthful representational world, highlighting what they think and what feel, something often silenced within school walls. In this sense, we discuss not only about the existence of a single youth, but of diverse and multiple “youths” Dayrell (2003; 2007). The techniques used include: participant observation, use of field diaries, informal conversation circles, photographic records and textual production. The bibliographic survey and review for the construction of the theoretical framework focused on studies that deal with the areas: “youth”, “youth protagonism”, “school”, “social networks”, “social representations”.